Work Environment Evaluation by Nurses and its Connection to Employee Turnover - Rukštavičiūtė, Indrė; Vimantaitė, Renata (Slauga. Mokslas ir praktika, 2022)
The working environment for nurses is being studied all around the world because of nursing staff turnover and increasing shortage of nurses. Healthy work environments establishment and maintenance is important for the well-being of nurses, their being in the organization, and the quality of patient care. Any change in this group may lead to a decrease in the efficiency of the organization.The aim of the study was to investigate how do nurses evaluate work environment and how it‘s linked with employee turnover.Methodology. Quantitative research was performed, the method of questionnaire survey was applied. There were 143 questionnaires filled by nurses in tertiary level hospital. For environment evaluation Eilen T. Lake's practice environment scale of the nursing work index was used, the rest of the questions were based on literature sources.Results. The working environment of nurses is generally favorable in most of the departments, only one department’s environment was rated as mixed work environment. The largest number of nurses employed in 2017-2020 time period was in intensive care units, and the highest number of nurses who left at the same time period were in therapeutic wards. The desire to accept another job offer and to consider staying or leaving the department among nurses was affected by nursing managers, their skills, leadership, support, human and work resources.Conclusions. This study confirms strong links between nursing leadership, human and work resources distribution, nursing staff turnover.
Keywords: nurse; work environment; nurses view